Concordance of SARS-CoV-2 Results in Self-collected Nasal Swabs vs Swabs Collected by Health Care Workers in Children and Adolescents - Waggoner, Jesse J; Vos, Miriam B; Tyburski, Erika A; Nguyen, Phuong-Vi; Ingersoll, Jessica M; Miller, Candace; Sullivan, Julie; Griffiths, Mark; Stone, Cheryl; Benoit, Macarthur; Benedit, Laura; Seitter, Brooke; et al. (JAMA : the journal of the American Medical Association, 2022)
IMPORTANCE: Despite the expansion of SARS-CoV-2 testing, available tests have not received Emergency Use Authorization for performance with self-collected anterior nares (nasal) swabs from children younger than 14 years because the effect of pediatric self-swabbing on SARS-CoV-2 test sensitivity is unknown. OBJECTIVE: To characterize the ability of school-aged children to self-collect nasal swabs for SARS-CoV-2 testing compared with collection by health care workers. DESIGN, SETTING, AND PARTICIPANTS: Cross-sectional study of 197 symptomatic children and adolescents aged 4 to 14 years old. Individuals were recruited based on results of testing in the Children’s Healthcare of Atlanta system from July to August 2021. EXPOSURES: Children and adolescents were given instructional material consisting of a short instructional video and a handout with written and visual steps for self-swab collection. Participants first provided a self-collected nasal swab. Health care workers then collected a second specimen. MAIN OUTCOMES AND MEASURES: The primary outcome was SARS-CoV-2 detection and relative quantitation by cycle threshold (Ct) in self- vs health care worker–collected nasal swabs when tested with a real-time reverse transcriptase–polymerase chain reaction test with Emergency Use Authorization. RESULTS: Among the study participants, 108 of 194 (55.7%) were male and the median age was 9 years (IQR, 6-11). Of the 196 participants, 87 (44.4%) tested positive for SARS-CoV-2 and 105 (53.6%) tested negative by both self- and health care worker–collected swabs. Two children tested positive by self- or health care worker–collected swab alone; 1 child had an invalid health care worker swab. Compared with health care worker–collected swabs, self-collected swabs had 97.8% (95% CI, 94.7%-100.0%) and 98.1% (95% CI, 95.6%-100.0%) positive and negative percent agreement, respectively, and SARS-CoV-2 Ct values did not differ significantly between groups (mean [SD] Ct, self-swab: 26.7 [5.4] vs health care worker swab: 26.3 [6.0]; P = .65). CONCLUSIONS AND RELEVANCE: After hearing and seeing simple instructional materials, children and adolescents aged 4 to 14 years self-collected nasal swabs that closely agreed on SARS-CoV-2 detection with swabs collected by health care workers.